Estrategias didácticas para el aprendizaje significativo en la asignatura de lengua y literatura en niños de quinto año de educación general básica de la unidad educativa “23 de Abril”, de la parroquia Santa Fe de la ciudad de Guaranda, provincia Bolívar, durante el año 2022 - Caguano Chillagana, Karla Marianela (2022)
The lack of application of didactic strategies in the subject of Language and Literature affects meaningful learning and of course the development of a good teaching environment within the classroom in the boys and girls of the Fifth year of Basic Education in the Educational Unit "23 de April” of the Santa Fe parish of the Guaranda canton. That is why there is a need to require teachers to practice or apply new techniques or teaching methods to strengthen students' knowledge and achieve meaningful learning. This investigative report addresses the use of didactic strategies to improve and create significant learning in students, in addition, through the inquiry it will be possible to identify if the teacher correctly uses and implements these teaching learning methods or techniques for the development of motivational skills and abilities in students. students of the fifth year of EGB, likewise the degree of knowledge that the students have acquired during the process will be evaluated, evidencing the good use of didactic techniques and the evolution of significant learning. To determine and evidence the problem that has arisen in the educational unit "April 23", a survey was conducted to the students which allowed to identify and capture the results obtained from this research, using a quantitative approach to deepen the analysis of the problem. problem taking into account both the deductive and inductive method for a better understanding in the analysis and interpretation of statistical results. Within the results obtained, the problem that both teachers and students face in one way or another is clearly evident and the study of this case was considered important, since students need optimal teaching and learning in their training. 11 In this way, it is of great importance that people are interested in the learning process of the students and can give a better solution to this process that is considered should continue to be studied, since the use and application of the techniques is essential. of teaching within the education process and especially in the subject of Language and Literature and those students manage to obtain learning in a significant way through efficient and effective teaching and this is achieved with the joint work between teachers and students. Finally, it is recommended that teachers apply new teaching methods and techniques that will favor learning and the knowledge required in the students of the entire educational unit and not just a few, since, in this way, the existing and evident gaps will be enriched. in this educational process.